Books donation program - Siti Sarah, Mohamad Rajimi (2017)
Mandarin Language Society donated 1981 books to four selected library in Pahang in a recent event held at UMP Pekan Library Auditorium. UMP Chief Librarian, Haji Ruslan Che Pee officiated the ceremony and handed over the donation to Sekolah Jenis Kebangsaan Cina (SJKC) Yoke Hwa, SJKC Kemasul, SJKC Kong Ming and Pahang State Library.